2022
DOI: 10.1002/lpor.202200057
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Transition Metal Dichalcogenide Multilayers for Advanced Nanophotonics

Abstract: Transition metal dichalcogenides (TMDs) attract significant attention due to their exceptional optical, excitonic, mechanical, and electronic properties. Nanostructured multilayer TMDs were recently shown to be highly promising for nanophotonic applications, as motivated by their exceptionally high refractive indices and optical anisotropy. Here, this vision is extended to more sophisticated structures, such as periodic arrays of nanodisks and nanoholes with ultra sharp walls, as well as proof‐of‐concept all‐T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…32,72,73 The understanding of the mechanisms for the enrichment of TMD crystals with zigzag edges is also important for the development of next-generation nanopatterned catalysts, stretchable gas-sensing films, and metamaterials for all-TMD nanophotonics. 74,75 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…32,72,73 The understanding of the mechanisms for the enrichment of TMD crystals with zigzag edges is also important for the development of next-generation nanopatterned catalysts, stretchable gas-sensing films, and metamaterials for all-TMD nanophotonics. 74,75 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…34 All-2D material integrated nanophotonics is envisioned as a result of the recent interest in such 2D-based optical systems. 35,36 Light will be absorbed, contained, guided, and detected by an all-2D integrated chip. All-2D devices can provide a reduced footprint, greater energy efficiency, and enhanced light–matter interactions.…”
Section: Perspective and Discussionmentioning
confidence: 99%
“…COMMUNICATION applications including lasers, 27,28 waveguides, 25,29,30 high harmonic generation, [30][31][32] bound states in the continuum, 33,34 etc.…”
Section: Nanoscale Horizonsmentioning
confidence: 99%
“…Most recent studies have revealed many new outstanding properties of multilayered TMDCs, such as their giant optical anisotropy, 21 polarizing effects, 22 anapole–exciton polaritons, 23 exciton–plasmon–polaritons, 24 exciton–polariton transport, 25 second harmonic generation, 26 etc. All the above-mentioned properties make these materials a perfect candidate for a variety of nanophotonic applications including lasers, 27,28 waveguides, 25,29,30 high harmonic generation, 30–32 bound states in the continuum, 33,34 etc.…”
Section: Introductionmentioning
confidence: 99%